Link Between Migration Status and Occupational Health and Safety of Filipino Migrant Workers in South Korea. - Amit, Lito M.
With its offer of competitive compensation and attractive employment permit system (EPS), South Korea has recently experienced an influx of migrant workers. There has been a concomitant rise in the concerns about the health and safety of migrant (especially undocumented) workers as well. The purpose of this study was to identify the prevalence of work-related health and safety problems among Filipino migrant workers and determine the relationship between migration status and occupational health and safety (OHS) problems. We conducted a survey of 116 Filipino migrant workers, both legal and undocumented. We utilized the Korean Occupational Stress Scale (KOSS), Nordic Musculoskeletal Questionnaire (NMQ), and a validated health and safety questionnaire to assess the various forms of occupational health problems they face. A focus group discussion (FGD) was also conducted to cross-validate information from the questionnaire. Descriptive data were presented in percentages, mean, and standard deviation (SD). Chi-squares tests and logistic regression analyses were performed to estimate the degree of association between variables (P < 0.05). Among the eight subscales of KOSS, inadequate social support (2.48), organizational injustice (2.57), and lack of reward (2.52) were experienced by workers. There was a 44.83% prevalence of musculoskeletal disorders (MSDs) with the arm/elbow having the highest rate, followed by the shoulder and low back regions. Inadequate social support and discomfort in organizational climate and overall MSDs prevalence showed significant relationships with migration status (P < 0.05). A significant relationship between migration status and some of the OHS problems faced by Filipino migrant workers in Korea was observed. In this study, undocumented workers were seen to be more vulnerable to stressors as compared to those employed legally.